ONE-PRONG TAU-DECAYS WITH NEUTRAL KAONS - Acciarri, M; Adam, A; Adriani, O; Aguilarbenitez, M; Ahlen, S; Alpat, B; Alcaraz, J; Allaby, J; Aloisio, A; Alverson, G; Alviggi, M; Ambrosi, G; et al. (1995)
We have analyzed one-prong τ decays with neutral kaons using the information from a fine-grained hadron calorimeter. The data sample consists of 43 500 Z → τ+τ-(γ) events collected by the L3 detector at LEP in 1991, 1992 and 1993. The following branching fractions are measured: B(τ- → ντπ-K0) = 0.0095 ± 0.0015(stat) ± 0.0006(syst); B(τ- → ντπ- π0K0) = 0.0041 ± 0.0012(stat) ± 0.0003(syst) and B(τ- → ντπ-K0K0) = 0.0031 ± 0.0012(stat) ± 0.0004(syst). © 1995.